2004
DOI: 10.1091/mbc.e04-07-0571
|View full text |Cite
|
Sign up to set email alerts
|

A NIMA-related Kinase, Fa2p, Localizes to a Novel Site in the Proximal Cilia ofChlamydomonasand Mouse Kidney Cells

Abstract: Polycystic kidney disease and related syndromes involve dysregulation of cell proliferation in conjunction with ciliary defects. The relationship between cilia and cell cycle is enigmatic, but it may involve regulation by the NIMA-family of kinases (Neks). We previously showed that the Nek Fa2p is important for ciliary function and cell cycle in Chlamydomonas. We now show that Fa2p localizes to an important regulatory site at the proximal end of cilia in both Chlamydomonas and a mouse kidney cell line. Fa2p al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 57 publications
4
75
0
Order By: Relevance
“…Fa2p, a NIMA-related kinase important for cilia disassembly, localized to proximal segment of the cilia in Chlamydomonas. 5 Our data showed that Nek 8 regulates cilium length and restricts polycystins entering cilia. Together with the specific localization of Nek8 to the proximal segment of primary cilia, it is tempting to hypothesize that the proximal segment may be an important site for gating the entry of proteins to the shaft of cilia.…”
Section: (Yl and Jz Unpublished Observations)mentioning
confidence: 59%
See 1 more Smart Citation
“…Fa2p, a NIMA-related kinase important for cilia disassembly, localized to proximal segment of the cilia in Chlamydomonas. 5 Our data showed that Nek 8 regulates cilium length and restricts polycystins entering cilia. Together with the specific localization of Nek8 to the proximal segment of primary cilia, it is tempting to hypothesize that the proximal segment may be an important site for gating the entry of proteins to the shaft of cilia.…”
Section: (Yl and Jz Unpublished Observations)mentioning
confidence: 59%
“…4 Recently, Fa2p was found localized to the proximal end of cilia, in both Chlamydomonas and cultured kidney epithelial cells, and its kinase activity is required for deflagellation. 5 To date, 11 Nek family members have been cloned from mouse or human cells, of which Nek2 is considered to be the closest NIMA homolog and therefore has been the most intensively studied.…”
mentioning
confidence: 99%
“…fa2 mutants are slow to transit the cell cycle owing to a G2-M delay and do not sever the nine outer doublet microtubules of the axoneme in response to deflagellation stimuli (Finst et al, 1998;Mahjoub et al, 2002). During interphase, Fa2p localizes to the proximal end of the flagella, whereas during mitosis it is associated with the polar region of the mitotic spindle (Mahjoub et al, 2004). This was the first report of a NIMA-related kinase with both cell cycle and ciliary functions; Cnk2p is the second.…”
mentioning
confidence: 78%
“…Fa2p is restricted to the transitional region between the BB and the axoneme (Mahjoub et al, 2004), and FA2 mutants are defective in flagellar autotomy, a process that is triggered by microtubule severing in the transitional region (Mahjoub et al, 2002). We show here that Nrk17p is mainly localized with the BBs and the most proximal part of the cilium.…”
Section: Discussionmentioning
confidence: 99%